Measuring New Zealand's Productivity - Erwin Diewert; Denis Lawrence (New Zealand Government, The Treasury, 1999)
This report was prepared for the Department of Labour, Reserve Bank of New Zealand and Treasury by Dr Denis Lawrence (Tasman Asia Pacific) and Professor Erwin Diewert (University of British Columbia) under contract. The authors examine New Zealand's market sector productivity performance using two databases. One has been prepared by the authors and contains a large number of input and output variables for the period 1972 to 1998. The second database involves data provided to the authors by officials and allows estimates to be prepared for 20 individual market sectors over the period 1978 to 1998. The authors provide estimates of New Zealand's total factor, labour and capital productivity, using an index number based methodology. They carry out many sensitivity tests relating to different input, output and functional form specifications. Labour input specifications are found to be important. The results are compared with Australian and OECD estimates and tested for structural breaks over time. Other recent New Zealand contributions to productivity literature are reviewed and statistical measurement problems are discussed. The data and techniques used are fully documented.
Keywords: 330